Eksplorasi Interaksi Digital Marketing dan Personal Selling dalam Mempengaruhi Keputusan Pembelian Produk Kecantikan - Paratama Kurniawan; Mitra Riani Aisyah (Scimadly Publishing, 2023)
Ms.Glow beauty products is a business focused on skin care and beauty. In the marketing efforts of MS.GLOW products, digital marketing strategies and personal selling are utilized to influence consumer purchasing decisions. The objectives of this research are as follows: (1) to determine whether digital marketing influences purchasing decisions, (2) to explore how personal selling affects purchasing decisions, (3) to investigate whether digital marketing simultaneously affects purchasing decisions. In this study, a quantitative correlation method is employed to analyze the data. The population of this research consists of all consumers who purchase MS.GLOW products at Cut Rafa Aek Nabara store, and the sample for this study represents the population with a sample size of 60 individuals. The sampling technique used in this study is saturated sampling. Statistical analysis is employed for data analysis. The research findings indicate that both digital marketing and personal selling variables influence consumer purchasing decisions, with a coefficient value of Y = 0.909 + 0.836X and a significance level of a less than 0.06. Additionally, the statistical calculations in the summary model reveal an R Square value of 0.732, indicating that digital marketing and personal selling have an influence on purchasing decisions.